EVALUASI PERENCANAAN DALAM PENGEMBANGAN ORGANISASI BERIMPLIKASI PENINGKATAN PEREKONOMIAN MASYARAKAT KEPULAUAN NIAS MELALUI KOPERASI KONSUMEN OSSEDA FAOLALA PEREMPUAN NIAS - Harefa, Animan; Ndraha, Ayler Beniah (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract. Evaluation is one of a series of activities to improve the quality and performance or productivity of an institution in implementing a program. Organizational Development (PO) is a long-term planning program and process that brings transformational change in organizational culture through the use/application of research and theories based on Information Technology and Science. The Osseda Faolala Perempuan Nias Consumer Cooperative has become a center for women's education & learning, especially for members of the Osseda Faolala Perempuan Nias Cooperative through various capacity building activities in the form of training (TOT), critical awareness discussions or courses aimed at increasing women's leadership potential so that they are able to involve themselves & become takers. decisions either in government agencies or non-government agencies. The obstacles faced by the Osseda Faolala Women's Nias Consumer Cooperative are caused by the Vision and Mission and the rule from year to year that membership is only women in accordance with the Vision and Mission that has been developed. It can be concluded that the problem is that it collides with the rules that have been established since time immemorial, especially the Vision and Mission that have been created and continue to be adopted to this day, however, they do not address the dynamics of the needs of the community, especially the Nias Islands. The results of this research are that the Osseda Faolala Perempuan Nias Cooperative has a good understanding of effectiveness, especially in the context of planning and evaluation. Their efforts to correct discrepancies between plans and results, as well as awareness of changes in the external environment, demonstrate a mature approach to managing challenges. A good understanding of challenges and changes, strong collaboration with stakeholders, a high level of member participation, and holding a scheduled Annual Membership Meeting every year are important elements that enable an organization to address and overcome challenges, maintain transparency, and achieve goals community economic development.